Relationship between employee motivation and job performance / Nur Amalina Azyan Jamaldin and Nur Syafiqa Suhandi - Jamaldin, Nur Amalina Azyan; Suhandi, Nur Syafiqa (2018)
This study is carried out to investigate the factors of motivation towards employee’s job performance. This chapter will included the background of the research, problem statement of the study, research objectives, research question and scope of the study. Other than that, in this chapter we also will discuss on significance of the study and the definition of terms and concepts that are being use in this study.